KAEDAH BACAAN RIWAYAT WARSY - Jabir, Muhammad (Institut Agama Islam Negeri (IAIN) Palu, 2007)
According to historical record, qiraah al-Quran, had existed since the revelation of the Quran. Nevertheless, not until the early second century of Hijriyah did its distribution to various other parts of the Islamic worldÂ begin. The qiraath was taughtÂ Â from generation to generation till the epoch of Imam of qirâah.Â Majmaul Buhus (Research Institute) of Al-Azhar, Cairo, in its congress dated 20-27th Â April, 1971, had decided that qiraah al-Quran wasÂ tauqifiy (Devine ordain) deriving from ruwat al-mutawatirah. For this reason, the congress recommended that the Islamic states not recite the Quran using one kind of qiraâah only, that is riwayat hafsh version. The purpose was to preserve other qiraahÂ from its extinct.Kata Kunci: Riwayat warsy, qiraah al-Qurâan, farsyul huruf